Reviews. Issue 1 (1st April 2019) - Guo, Ting; Kimbrough, Andrew; Duchan, Joshua S.; Young, Miriama; Tebbutt, John
The Sociolinguistics of Voice in Globalising China, Dong Jie (2017) London and New York: Routledge, 160 pp., ISBN 978-1-13879-880-9, h/bk, £115.00Theatre & Voice, Konstantinos Thomaidis (2017) London: Palgrave, 89 pp., ISBN 978-1-13755-249-5, USD 17.99, £ 6.99Karaoke Idols: Popular Music and the Performance of Identity, Kevin Brown (2015) Bristol: Intellect, xvii + 152 pp., ISBN 978-1-78320-444-1, p/bk, 36Postopera: Reinventing the Voice-Body, Jelena Novak (2015) Ashgate Interdisciplinary Studies in Opera, Dorchester: Ashgate, 192 pp., ISBN 978-1-47244-103-4, h/bk, 120; ISBN 978-1-13850-496-7, p/bk, 49.95The Voice and its Double: Media and Music in Northern Australia, Daniel Fisher (2016) Durham and London: Duke University Press, 320 pp., ISBN 978-0-82236-086-9, h/bk, 99.95; ISBN 978-0-82236-120-6, p/bk, 26.95